2023
DOI: 10.1371/journal.pone.0280084
|View full text |Cite
|
Sign up to set email alerts
|

Induced abortion among female students in higher education institutions in Ethiopia: A systematic review and meta-analysis

Abstract: Background Female students in institutions of higher education are at higher risk of abortion and its consequences. There is no nationally representative data on induced abortion among students in higher education institutions in Ethiopia. Hence, this study aimed to estimate the pooled prevalence of induced abortion among female students in institutions of higher education in Ethiopia. Methods This study used a systematic review and meta-analysis of studies conducted from January 1, 2010, to June 30, 2022, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(47 reference statements)
0
0
1
Order By: Relevance
“…The result of this study is much higher than the studies carried out in the Globe and Ethiopia with the same study design, which revealed 5.81% and 5.06% [66,67] respectively. Similarly, studies conducted in East Africa, worldwide in 2010-14, Sierra Leone, Indonesia, Iran, Turkey, Ethiopia, and Australia revealed that 7.79%, 35 abortions occurred annually per 1000 women, 9%, 42.5 abortions per 1,000 women, 3.8%, 10.9%, 23 per 1,000 women and 2.1/100 women [68][69][70][71][72][73][74][75] respectively.…”
Section: Plos Onecontrasting
confidence: 78%
“…The result of this study is much higher than the studies carried out in the Globe and Ethiopia with the same study design, which revealed 5.81% and 5.06% [66,67] respectively. Similarly, studies conducted in East Africa, worldwide in 2010-14, Sierra Leone, Indonesia, Iran, Turkey, Ethiopia, and Australia revealed that 7.79%, 35 abortions occurred annually per 1000 women, 9%, 42.5 abortions per 1,000 women, 3.8%, 10.9%, 23 per 1,000 women and 2.1/100 women [68][69][70][71][72][73][74][75] respectively.…”
Section: Plos Onecontrasting
confidence: 78%
“…Approximately one-fifth of respondents in our study reported ever experiencing an unwanted pregnancy, and 14% reported having had an abortion. These numbers are higher than past research; a recent meta-analysis identified a pooled prevalence of induced abortion among female university students at 5.1% (36), however the magnitude of induced abortion at universities in Ethiopia ranged from 2.8% to 18.8% across studies (37,38). We found that SRH information and services were limited at the four universities, and often considered by both students and key informants to be of poor quality.…”
Section: Discussioncontrasting
confidence: 63%